1974
DOI: 10.3758/bf03334287
|View full text |Cite
|
Sign up to set email alerts
|

A classically conditionable skeletal response can be acquired with a discriminated punishment contingency

Abstract: Human Ss were exposed to a discriminated punishment contingency with the aversive stimulus being an air puff to the cornea. In most Ss there was an increase in response probability (an eyelid reflex) across trials and an application of the two-phase model showed that the increases, though not great, were reliable. An analysis of the estimated parameter values showed that for only 5 of the 26 Ss did the pattern of parameter values conform to what would be expected on the basis of either two-factor or relative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1975
1975
1984
1984

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Clark (1974) replicated this result in humans. Second, Prokasy, Clark, Williams, and Spurr (1974) found that humans will acquire a conditioned eyelid reflex even when exposed to a discriminated punishment contingency. These two results, in conjunction with the present data, make law-of-effect interpretations of CR acquisition and maintenance highly untenable for the rabbit and human aversive conditioning preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Clark (1974) replicated this result in humans. Second, Prokasy, Clark, Williams, and Spurr (1974) found that humans will acquire a conditioned eyelid reflex even when exposed to a discriminated punishment contingency. These two results, in conjunction with the present data, make law-of-effect interpretations of CR acquisition and maintenance highly untenable for the rabbit and human aversive conditioning preparations.…”
Section: Discussionmentioning
confidence: 99%